Water-Soluble Glutamic Acid Derivatives Produced in Culture by Penicillium solitum IS1-A from King George Island, Maritime Antarctica - Rodriguez, Julie P. G.; Bernardi, Darlon I.; Gubiani, Juliana R.; Oliveira, Juliana Magalhaes de; Morais-Urano, Raquel P.; Bertonha, Ariane F.; Bandeira, Karin F.; Bulla, Jairo I. Q.; Sette, Lara D. [UNESP]; Ferreira, Antonio G.; Batista, Joao M.; Silva, Thayna de Souza; et al. (Amer Chemical Soc, 2020)
A new method of screening was developed to generate 770 organic and water-soluble fractions from extracts of nine species of marine sponges, from the growth media of 18 species of marine-derived fungi, and from the growth media of 13 species of endophytic fungi. The screening results indicated that water-soluble fractions displayed significant bioactivity in cytotoxic, antibiotic, anti-Leishmania, anti-Trypanosoma cruzi, and inhibition of proteasome assays. Purification of water-soluble fractions from the growth medium of Penicillium solitum IS1-A provided the new glutamic acid derivatives solitumine A (1), solitumine B (2), and solitumidines A-D (3-6). The structures of compounds 1-6 have been established by analysis of spectroscopic data, chemical derivatizations, and vibrational circular dichroism calculations. Although no biological activity could be observed for compounds 1-6, the new structures reported for 1-6 indicate that the investigation of water-soluble natural products represents a relevant strategy in finding new secondary metabolites.